Cy3-RgIA-5727 Labels and Inhibits α9-Containing nAChRs of Cochlear Hair Cells - Fisher, Fernando; Zhang, Yuanyuan; Vincent, Philippe F. Y.; Gajewiak, Joanna; Gordon, Thomas J.; Glowatzki, Elisabeth; Fuchs, Paul Albert; McIntosh, J. Michael (Frontiers in Cellular Neuroscience, 2021)
Efferent cholinergic neurons inhibit sensory hair cells of the vertebrate inner ear through the combined action of calcium-permeable α9α10-containing nicotinic acetylcholine receptors (nAChRs) and associated calcium-dependent potassium channels. The venom of cone snails is a rich repository of bioactive peptides, many with channel blocking activities. The conopeptide analog, RgIA-5474, is a specific and potent antagonist of α9α10-containing nAChRs. We added an alkyl functional group to the N-terminus of the RgIA-5474, to enable click chemistry addition of the fluorescent cyanine dye, Cy3. The resulting peptide (Cy3-RgIA-5727) potently blocked mouse α9α10 nAChRs expressed in Xenopus oocytes (IC50 23 pM), with 290-fold less activity on α7 nAChRs and 40,000-fold less activity on all other tested nAChR subtypes. The tight binding of Cy3-RgIA-5727 provided robust visualization of hair cell nAChRs in excised, unfixed cochlear tissue from mice. Presumptive postsynaptic sites on outer hair cells were labeled, but absent from inner hair cells and from outer hair cells in cochlear tissue from α9-null mice and in cochlear tissue pre-incubated with non-Cy3-conjugated RgIA-5474. In cochlear tissue from younger (postnatal day 10) mice, Cy3-RgIA-5727 also labeled inner hair cells, corresponding to transient efferent innervation at that age. Nonspecific labeling of stereocilia and within surrounding tissue remained in the α9-null tissue. Pre-exposure with non-Cy3-conjugated RgIA-5474 eliminated this nonspecific labeling to variable extents in different preparations. The fluorophore-conjugated conopeptide retained its blocking potency in tests on the native hair cell nAChRs, within the constraints of application to the excised cochlear tissue. RgIA-5474 and RgIA- 5727 block of efferent synaptic currents in young inner hair cells was not relieved after 50 minutes washing, so effectively irreversible.